Farming systems influence the compositional, structural, and functional characteristics of the sugarcane-associated microbiome - de Carvalho, Lucas Amoroso Lopes [UNESP]; Teheran-Sierra, Luis Guillermo [UNESP]; Funnicelli, Michelli Inácio Gonçalves [UNESP]; da Silva, Rafael Correia [UNESP]; Campanari, Maria Fernanda Zaneli [UNESP]; de Souza, Rafael Soares Correa; Arruda, Paulo; Soares, Marcos Antônio; Pinheiro, Daniel Guariz [UNESP] (Elsevier, 2021)
Sugarcane (Saccharum spp.) has been produced worldwide as a relevant source of food and sustainable energy. However, the constant need to increase crop yield has led to excessive use of synthetic agrochemical inputs such as inorganic fertilizers, herbicides, and pesticides in plant cultures. It is known that these conventional practices can lead to deleterious effects on health and the environment. Organic farming emerges as a sustainable alternative to conventional systems; however, farm management influences in plant-associated microbiomes remain unclear. Here, the aim is to identify the effects of farming systems on the sugarcane microbiota. To address this issue, we sampled the microbiota from soils and plants under organic and conventional farming from two crop fields in Brazil. Then, we evaluated their compositional, structural, and functional traits through amplification and sequencing of phylogenetic markers of bacteria (16S rRNA gene, V3-V4 region) and fungi (Internal Transcribed Spacer - ITS2). The data processing and analyses by the DADA2 pipeline revealed 12,839 bacterial and 3,222 fungal sequence variants. Moreover, differences between analogous niches were detected considering the contrasting farming systems, with samples from the conventional system showing a slightly greater richness and diversity of microorganisms. The composition is also different between the farming systems, with 389 and 401 differentially abundant taxa for bacteria and fungi, respectively, including taxa capable of promoting plant growth. The microbial co-occurrence networks showed structural changes in microbial communities, where organic networks were more cohesive since they had closer taxa and less modularity by niches. Finally, the functional prediction revealed enriched metabolic pathways, including the increased presence of antimicrobial resistance in the conventional farming system. Taken together, our findings reveal functional, structural, and compositional adaptations of the microbial communities associated with sugarcane plants in the field, according to farming management. With this, we point out the need to unravel the mechanisms driving these adaptations.
Keywords: Metabarcoding; Microbial network; Organic farming; Sugarcane microbiome; Sustainability